2018
DOI: 10.1215/9780822372073
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming the Discarded

Abstract: In Reclaiming the Discarded Kathleen M. Millar offers an evocative ethnography of Jardim Gramacho, a sprawling garbage dump on the outskirts of Rio de Janeiro, where roughly two thousand self-employed workers known as catadores collect recyclable materials. While the figure of the scavenger sifting through garbage seems iconic of wageless life today, Millar shows how the work of reclaiming recyclables is more than a survival strategy or an informal labor practice. Rather, the stories of catadores show how this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(39 citation statements)
references
References 0 publications
0
38
0
1
Order By: Relevance
“…Such entanglements of formal and informal economic activity, the use of incommensurable national metrics, and the supposed failure of the binary to say much about workers' experience of their own labour have led some scholars to abandon it entirely (e.g. Millar, ). The current intellectual trend is to address the question of precarity instead, although this concept has its own weaknesses (see Breman, ; Munck, ).…”
Section: Discussing (In)formalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such entanglements of formal and informal economic activity, the use of incommensurable national metrics, and the supposed failure of the binary to say much about workers' experience of their own labour have led some scholars to abandon it entirely (e.g. Millar, ). The current intellectual trend is to address the question of precarity instead, although this concept has its own weaknesses (see Breman, ; Munck, ).…”
Section: Discussing (In)formalitymentioning
confidence: 99%
“…According to Medina's (: 17) classification of state approaches to waste‐picking, such policies are an example of ‘stimulation’, in that they recognise ‘the economic, social, and environmental benefits of scavenging and recycling’. Yet recent studies have also questioned whether the inclusion of waste‐pickers in waste management schemes in places like Soweto, Rio de Janeiro, and Buenos Aires is beneficial for workers and ultimately contributes to social justice (Sternberg, ; Samson, ; Millar, ).…”
mentioning
confidence: 99%
“…5 Scavenging today, particularly in the urban Global South, has been portrayed as ' an adaptive response to scarcity' by people who lack other means of provisioning (Medina 2001: 238). Reclaiming waste from households, at landfill sites or in areas of the urban landscape is often regarded as a stigmatizing economic strategy of the urban poor (Millar 2018). However, pressure on resources and problems with the accumulation of waste has led to the emergence of a kind of gentrified scavenging in the context of Northern European redesign, where it is mainly driven by ideological, environmental and aesthetic concerns (Ottosson 2008).…”
Section: Sourcing and Scavengingmentioning
confidence: 99%
“…Indeed, numerous ethnographies have already illustrated the deeply relational, situated and cultural entanglements implied in the determination of 'resource' 'value' and 'waste' among a wide variety of communities for whom the concept of circular economy is considered common sense. From ethnographies featuring innovative reuse among resource-strapped communities (Nguyen, 2016) and garbage pickers on the margins of Brazilian society (Millar, 2018) to sanitary workers in New York City (Nagle, 2014), or among connoisseurs of thrift shops and vintage goods (Appelgren and Bohlin, 2015;Isenhour, 2012), these studies have long demonstrated the not-so-novel concept of informal circular economies in action.…”
mentioning
confidence: 99%